IMMUNE AND CYTOKINE STATUS IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA RECEIVING ALEMTUZUMAB - M. N Khorobrykh (Medicinskaâ Immunologiâ, 2014)
In present work, we studied cytokine levels and performed analysis of some immunologic parameters in the patients with chronic lymphocytic leukemia (CLL) before and after treatment with monoclonal anti-CD52 antibody (alemtuzumab). In comparison with a control group, the CLL patients before alemtuzumab treatment showed a significant decrease in relative contents of CD3+ and CD4+ lymphocytes, CD4+/CD8+ T cells, diminished IFNγ and IL-4 levels, and a trend for TNFα increase. After ceasing the alemtuzumab treatment, the patients with CLL exhibited a significant decrease in absolute amounts of mature T-lymphocytes, CD4+, CD8+, CD20+ cells, as well as decreased relative contents of CD16+ lymphocytes. A sufficient post-treatment drop of serum IL-2 concentrations and a trend for serum TNFα and IFNγ decrease were also observed, as compared with pre-treatment values. The changes revealed may be connected with an additional immunosuppressive effect of alemtuzumab. The dynamics of cytokine levels and immunological parameters associated with alemtuzumab treatment is indicative for a weakening of cell-mediated immunity, thus resulting into a potential risk of infectious complications.